A thermo-elastic-plastic phase-field model for simulating the evolution and transition of adiabatic shear band. Part I. Theory and model calibration. (1st June 2020) - Wang, T.; Liu, Z.L.; Cui, Y.N.; Ye, X.; Liu, X.M.; Tian, R.; Zhuang, Z.
Highlights: A thermo-elastic-plastic phase-field model is established to simulate the ASB. The damage parameters of phase-field model are calibrated using experimental data. The simulation results successfully explain the typical phenomena in the experiment. The model can quantitatively describe the temperature and damage evolution of ASBs. Abstract: Adiabatic shear band (ASB) is an important failure mode of solid materials, especially for metal materials under high strain rate loading. In this study, a thermo-elastic-plastic phase-field model, which considers both damage softening and thermal softening, is established to simulate the formation of multiple ASBs and the transition from ASB to the fracture. How to select and calibrate the material parameters in the phase-field model is seldom clearly discussed in the current phase-field model when dealing with ASB. In this paper, the damage parameters in the phase-field method are calibrated using data from pure shear specimens, taking into account both the overall response of the structure and the local response in the ASB. As an application, the calibrated model is used to numerically study the evolution of the ASB of the hat specimen and the process of its transition to the fracture. The simulation results successfully explain the typical phenomena such as transient "hot spots" and double softening in the experiment. The numerical model we developed provides a reliable quantitative description for the evolution and width calculation of ASBs and lays a foundation for the further study of ASB.